Pembelajaran antara Minat Membaca dan Motivasi Belajar Siswa Kelas V SDN Karolina - Ina Magdalena; Marifatul Ulfah; Siti Zaedatun Nikmah (AS-SABIQUN, 2020)
The development of learning to read can be done through the use of three channels of character education implementation, namely through teaching materials, learning models, and authentic assessment. Authentic assessment is the most important channel because the use of authentic assessment will include the selection of teaching materials and learning models. Authentic assessment guides learning through the creation of various learning activities carried out by students during the learning process which contains character content. Learning between Reading Interest and Learning Motivation of Class V SDN KAROLINA Students. The purpose of this study was to obtain clarity and objective information about learning between reading interest and learning motivation of grade V SDN KAROLINA students. The method used in this research is descriptive method with the form of research is a learning study. This means that there is significant learning between reading interest and learning motivation of grade V SDN KAROLINA students.